Agency costs and the long-run performance of debt issuers - Ibrahim, Yusnidah; Uddin, Md Mohan; Taufil Mohd, Kamarun Nisham; Minai, Mohd Sobri (Universiti Sains Malaysia, 2013)
This study focuses on an agency cost explanation of the long-run performance of debt issuers based on debt issuance data in Malaysia during the period from January 2001 to October 2009.Long-run performance is measured by buy and hold abnormal return (BHAR),while growth opportunities(GO), managerial ownership (MO), ownership concentration (OC) and free cash flow (FCF) are adopted as proxies for agency costs.Using a linear regression method, this study finds that BHAR is positively influenced by GO and OC but negatively influenced by MO and FCF, which supports an agency cost explanation of capital structure.An improvement in the performance of debt issuers is found to be associated with the monitoring of debt by debt issuers. Debt issuers with more concentrated ownership and lower MO benefit from the issuance of debt through a reduction of agency costs.